NUTRITIONAL VALUE OF CANNED FOOD WITH THE USE OF RABBIT MEAT FOR CHILDREN’S AND DIETARY FOOD - Atakhodjaeva , Inoyat (Educational Research in Universal Sciences, 2024)
The modern level of knowledge about food products allows them to be developed with specified properties that correspond to a specific purpose. The creation of such products is always a search for a reasonable compromise between the numerous requirements for food products. The article reflects the results of a scientific study devoted to the development of a recipe for canned meat for baby food with a different percentage of rabbit meat and vegetables. Comprehensive studies of the consumer properties of canned food obtained according to one of the author’s recipes were carried out. Microelements are basic and acidic in nature. The basic ones include calcium, magnesium, potassium, sodium, and the acidic ones include phosphorus, sulfur, and chlorine. The rabbit meat a white meat which contains macro nutrients and micro nutrients and it is a good source of minerals entering the human body is food products of plant and animal origin. Drinking water covers only up to 10% of the daily requirement for microelements such as J, Cu, Zn, Mn, Co, Mo, and only for individual microelements (F, Sr) can it serve as the main source of their intake into the body. The content of various microelements in the diet depends on the geochemical conditions of the area in which the products were obtained, as well as on the set of food products included in the diet.